Peranan Yayasan Bambu Lestari dalam Upaya Pemanfaatan Bambu sebagai Sumber Daya Ekonomi Bagi Masyarakat (Studi Kasus Kelompok Subinana, Desa Nginamanu, Kecamatan Wolomeze, Kabupaten Ngada) - Maria Erwinda Bouk; Ludji Michael Riwu Kaho; Norman P. L. B. Riwu Kaho; Roni Haposan Sipayung (Wana Lestari, 2024)
Non-Timber Forest Products abbreviated as NTFPS Bamboo in East Nusa Tenggara has considerable potential to affect people's lives, one of which is bamboo which can produces products that are used as an additional sources of production for the people of Nginamanu Village. This study aims to determined bamboo management and determined the roles of the Bambu Lestari Foundation in helping the people’s economic, especially Subinana weavers in Nginamanu Village. The method used in this study was qualitative method. The results of the study were obtained through the interview method assisted by an attached questionnaire. The results showed that the roles of Yayasan Bambu Lestari was to provide the socialization and training in woven bamboo, promoted weaving, plant bamboo seedlings with the community, provided woven training to elementary, junior and high school of children. The economic changes of the community after the existence of the Bambu Lestari Foundation felt by the weaving community are helping them in meeting their daily needs, in addition to the woven proceeds also help in paying their children's school fees.